PENGAWASAN BEA DAN CUKAI TERHADAP PEREDARAN ROKOK ILEGAL DI KOTA PEKANBARU - Edo Puja Pradana; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Supervision is the process in setting performance measures and taking actions that can support the achievement of the expected results in accordance with set performance tersebut.Sehubungan thereto Control and Service Office of Customs and Excise Medium Type B Pekanbaru is one of the agencies that are authorized to perform control the circulation of illegal cigarettes that circulate in the city of Pekanbaru. The phenomena that researchers have encountered are: there are still many outstanding nonThis study aims to illegal fre zone from other areas in the city Pekanbaru.mengetahui and analyze how to control the circulation of illegal cigarettes by the Office of Supervision and Customs Service Medium Type B Pekanbaru, and the factors that affect oversight. This research is descriptive qualitative where data collection is used with observation and interview methods.The study found that the supervision of the circulation of illegal cigarettes by the Office of Supervision and Customs Service Medium Type B Pekanbaru still less than optimal in overseeing the circulation of illegal cigarettes. It can be seen from the phenomenon of the problem and the fact supervision that occurred in the field. Because it can be seen much of her in circulation of illegal cigarettes that circulate in the city of Pekanbaru. Factors that influence the control of illegal cigarettes by the Office of Supervision and Customs Service Medium Type B Pekanbaru among other factors that influence the control of illegal cigarettes by the Office of Supervision and Customs Service Medium Type B Pekanbaru include internal factors (HR), division a task that is not maximized and satandar or benchmark to perform an oversight is not appropriate, and external factors here occurs on the part of traders or shopkeepers who are still free to sell the products of illegal cigarettes would not obey the rules.Keywords: Monitoring, Illegal Cigarettes.